Effect of pruning time, severity and tree aspects on harvesting period and fruit quality of low chilling peach (Prunus persica) - SINGH, AKATH; DEKA, B C; PATEL, R K; NATH, A; MULIEH, S R (The Indian Journal of Agricultural Sciences, 2012)
Studies were conducted to find out the effect of pruning severity, time and tree aspects on early fruiting, yield and quality characters of Partap peach. Ten years old grafted trees were pruned at fortnightly intervals, i e on 30 October, 15 November and 30 November with two pruning levels, i e 50% and 70% severity (retaining 50% and 30% shoot). Flowering and fruiting was earlier by 15 days in trees pruned on October 30. Fruit size and yield was recorded maximum in trees pruned on October 30 with 50% shoot retention, whereas quality characters, viz. Total soluble solids and acidity was higher in fruits obtained from trees pruned on November 30 with 50% shoot retention. Reducing, non-reducing and total sugars were highest in 50% severity on 30 October. Colour reflectance values were found highest in fruits obtained from trees pruned on October 30 with 50% severity. While comparing the different aspects of the tree, all the physico-chemical parameters were found maximum in fruits of east direction followed by south and minimum in west direction. It was concluded that low chilling peach Partap pruned on 30 October with 50% shoot retention yielded fruits 15 days earlier of superior quality in general and east and south direction of trees particular.